40 Transforming training with rota design. (31st October 2017) - Rice, Alexandra; Golightly, Ellen; Mary, Y Nirmala; Alexander, Claire; Curry, Lesley
Abstract : Background: The Simpson Centre for Reproductive Health is a tertiary Obstetrics and Gynaecology unit. The trainee rotas were complex and conflicted between service provision and training. Following a Deanery visit a Trainee's Committee was set up and rotas became trainee-led. The impact of rota design change has been followed closely since then. Drivers for Change: Patient safety concerns and reduced quality of care Senior issues accessing advanced training Undermining behaviour Juniors felt anonymous No team structure Deanery 'red flags' Objectives: Improve access to training opportunities Improve satisfaction with training Positively influence departmental moral How did we implement change? A trainee driven rota working group was established with senior support. Though this, provisional rota options were formulated and co-designed. Based on trainee feedback the following points were essential in the design: Rota template identical for all tiers creating 'rota buddies' Emergency teams with all on call work in blocks Formation of elective teams given continuity of consultant trainers Senior trainees running senior rota Consultant responsibility for junior rota Results: The Scottish training survey (STS) was utilised as a validated tool to measure outcomes. Team Culture Teaching Educational environment KEY 2016 2017 2016 2017 2016 2017 -†'/-†" 95% significant change in mean score =no significant change in mean score -†" performing poorly/-†'performing well above for this indicator Foundation ïƒª ïƒ© ïƒª ïƒ© = GPST = = = = = = O and G ST = ïƒ© ïƒ© = ïƒ© = Lessons Learnt: The team structure gave a sense of belonging, and trainees felt valued. There was a change of culture away from undermining behaviours and towards shared training goals. Access to training opportunities was made equitably, and increased continuity between trainees and trainers. It has measurably improved training and departmental culture which has impacted positively on the delivery of care.